2015
DOI: 10.1007/s10479-015-2026-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple analysis of the batch arrival queue with infinite-buffer and Markovian service process using roots method: $$ GI ^{[X]}/C$$ G I [ X ] / C - $$ MSP /1/\infty $$ M S P / 1 / ∞

Abstract: We consider a batch arrival infinite-buffer single-server queue with generally distributed inter-batch arrival times with arrivals occurring in batches of random sizes. The service process is correlated and its structure is governed by a Markovian service process in continuous time. The proposed analysis is based on roots of the associated characteristic equation of the vector-generating function of system-length distribution at a pre-arrival epoch. We also obtain the steady-state probability distribution at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…A single server is serving the customers according to a continuous-time Markovian service process (C-) with matrix representation (L 0 , L 1 ). For a detailed discussion on -, the readers are referred to Chaudhry et al [5]. Let us denote L(…”
Section: Description Of the Model: [ ] / -/1/∞ Queue And The Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…A single server is serving the customers according to a continuous-time Markovian service process (C-) with matrix representation (L 0 , L 1 ). For a detailed discussion on -, the readers are referred to Chaudhry et al [5]. Let us denote L(…”
Section: Description Of the Model: [ ] / -/1/∞ Queue And The Analysismentioning
confidence: 99%
“…The two processes -and -are convenient representations of a versatile Markovian point process or N-process; see Neuts [3] and Ramaswami [4]. Chaudhry et al [5] obtain stationary system-length distributions for the infinite-buffer batch arrival / -/1 queues at various epochs using roots. Further, Singh et al [6] have shown that it is beneficial to use roots rather than the matrixgeometric/matrix-analytic methods in terms of computation time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations